Do Works Councils Inhibit Investment ? - Schank, Thorsten; Addison, John T.; Schnabel, Claus; Wagner, Joachim (Industrial & Labor Relations Review, 2007)
Theory suggests that firms confront a hold-up problem in dealing with workplace unionism: unions will appropriate a portion of the quasi rents stemming from long-lived capital. As a result, firms may be expected to limit their exposure to rent seeking by reducing investments, among other things. Although there is some empirical support for this prediction in firm-level studies for the United States, we investigate whether this is also the case in the different institutional context of Germany where the works council is the analogue of workplace unionism. Using parametric and nonparametric methods and establishment panel data, we find no evidence that the formation (dissolution) of a works council has an unfavorable (favorable) impact on investmen
WiSo-Import:2015-03-26:1751
Keywords: Kohäsion